Intrinsic Capacity of Chinese Community-Dwelling Older Adults Using WHO Integrated Care for Older People (ICOPE) Framework: Structural Equation Model Analysis - Sun, Junjun; Amnatsatsue, Kwanjai; Srisuwan, Patsri; Kerdmongkol, Patcharaporn; Nityasuddhi, Dechavudh (Journal of primary care & community health, 2025)
This study aimed to examine the intrinsic capacity in Chinese older adults and its determinants (sociodemographic, lifestyle-related, environmental, and health-related factors) based on the WHO Integrated Care for Older People (ICOPE) framework. A cross-sectional community-based study was conducted among 485 community-dwelling older adults recruited from 4 community health service centers in Xinxiang City, Henan Province between August 2024 and February 2025. Intrinsic capacity was assessed across 5 domains: locomotion, cognition, vitality, psychology, and sensory capacity (hearing and vision). Structural equation model (SEM) was used to examine relationships among intrinsic capacity, sociodemographic factors, lifestyle, family support, social participation, healthcare access, and health conditions. More than a half of subjects were female (61.2%), married (84.7%), having less than high school education (52%), with a mean age of 73.7 years (SD = 5.5). About 55.9% showed intrinsic capacity impairment, with most impairment of cognition (49.9%), followed by vision (44.9%), hearing (23.7%), locomotion (22.5%), vitality (18.1%), and psychological capacity (13%). The SEM demonstrated good fit and explained 83% of the variance in intrinsic capacity. Significant determinants, ranked by effect size, included dietary habits (β = .544), age (β = -.303), pain (β = -.240), handgrip strength (β = .205), social participation (β = .181), access to healthcare services (β = .138), hospitalization (β = -.10), and physical exercise (β = .089). All paths in the model were statistically significant ( ' 0.05). The SEM analysis demonstrated that dietary habits, handgrip strength, social participation, access to healthcare services, and physical exercise were positively associated with intrinsic capacity, while age, pain, and hospitalization showed negative associations. These findings suggest that primary care approaches focusing on multi-domain interventions, particularly health promotion, self-care, and early screening, may be promising areas for future public health initiatives. Community-based programs integrating these modifiable factors should be prioritized to promote intrinsic capacity and functional independence among Chinese community-dwelling older adults.